Decrease the interval calving period using prostaglandin in dairy cattle. (Journal of Hama University, 2024)
The research deals with the study of the effect of synchronizing estrus by using the prostaglandin in dairy cows in order to decrease the rest period and the calving interval period. The observation of estrus in cows and inseminating them at the optimum time is one of the necessary steps to manage reproduction in the dairy herd. The cows were taken from one of the special breeding farms in the countryside of Al Qusayr, in Zyta district, which had given birth more than 80 days ago, without the appearance of estrus. The cows were examined by rectal palpation to ensure the presence of the corpus luteum. 30 cows were taken and those cows were divided into two groups, the first group (nx=23) group; the experiment and the second group (nc=7), the control group. The first group was injected with prostaglandin a dose of 500 µg intramuscularly and these cows were monitored for 3-4 days to determine the time of estrus occurrence. GnRH dose 50 µg intramuscularly immediately after insemination ˛ As for the 6 cows that did not show estrus after the first injection, the 6 cows were injected with prostaglandin again after 14 days from the date of the first injection and when estrus appeared, they were artificially inseminated with a dose of GnRH hormone. The control group injected 2 ml of physiological solution intramuscularly. The results of the study showed that there were significant differences at the value (P
Keywords: dairy cattle, calving interval, prostaglandin.